2012
DOI: 10.1371/journal.pone.0033894
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Modeling of an Induction Regimen for In Vivo Combined Testing of Novel Drugs against Pediatric Acute Lymphoblastic Leukemia Xenografts

Abstract: Current regimens for induction therapy of pediatric acute lymphoblastic leukemia (ALL), or for re-induction post relapse, use a combination of vincristine (VCR), a glucocorticoid, and l -asparaginase (ASP) with or without an anthracycline. With cure rates now approximately 80%, robust pre-clinical models are necessary to prioritize active new drugs for clinical trials in relapsed/refractory patients, and the ability of these models to predict synergy/antagonism with established therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 52 publications
0
59
0
2
Order By: Relevance
“…Leukemia engraftment and response to drug treatment were assessed by weekly enumeration of the proportion of human CD45 + cells in the peripheral blood (%huCD45) [5]. Owing to previous experience showing that low level dissemination of xenograft cells into the peripheral blood is associated with high level infiltration of bone marrow and spleen [19], drug treatments were initiated when the %huCD45 reached 1% and continued until the %huCD45 increased through the drug treatments or until animals experienced leukemia- or drug-related morbidity. The number of emerging chemoresistant xenograft lines compared with the number of mice inoculated is depicted in Supplementary Table E1 (online only, available at www.exphem.org).…”
Section: Methodsmentioning
confidence: 99%
“…Leukemia engraftment and response to drug treatment were assessed by weekly enumeration of the proportion of human CD45 + cells in the peripheral blood (%huCD45) [5]. Owing to previous experience showing that low level dissemination of xenograft cells into the peripheral blood is associated with high level infiltration of bone marrow and spleen [19], drug treatments were initiated when the %huCD45 reached 1% and continued until the %huCD45 increased through the drug treatments or until animals experienced leukemia- or drug-related morbidity. The number of emerging chemoresistant xenograft lines compared with the number of mice inoculated is depicted in Supplementary Table E1 (online only, available at www.exphem.org).…”
Section: Methodsmentioning
confidence: 99%
“…Development of patient-derived xenografts and assessment of in vivo drug efficacy ) and evaluated their in vivo sensitivity to PR-104 as a single agent or in combination with VXL in groups of 6-10 mice have been previously reported, 33,[35][36][37][38][39] and are described in detail in the supplemental Methods (available on the Blood Web site). PR-104 was supplied by Proacta Inc through the Cancer Therapy Evaluation Program of the National Cancer Institute, or by the Auckland Cancer Society Research Centre.…”
Section: Methodsmentioning
confidence: 99%
“…To gain a greater perspective of the efficacy of PR-104 in relation to established drugs used to treat pediatric ALL, we combined PR-104 with an induction-type VXL regimen that was previously optimized in our laboratory 35 Tables 1-2). The combination of VXL and PR-104 achieved LGDs of 34.5 to 49.5 days in the 3 xenografts, indicating that the combination was neither synergistic nor antagonistic, and also that PR-104 alone was just as effective.…”
Section: Pr-104/pr-104a Exhibited Profound Antileukemic Efficacy Agaimentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of mice was commenced when the proportion of human leukemia cells in the murine peripheral blood exceeded 1%, as we have previously shown that this level of engraftment represents a considerable overall disease burden in the animals. 12 PDX responses were assessed weekly by measuring the percentage of circulating human leukemia cells in mouse peripheral blood. PDX mice treated with SAR3419 and topotecan showed clearance of ALL from the peripheral blood at the end of the 1st week of treatment, 60 days after the 2nd relapse ( Table 1).…”
mentioning
confidence: 99%